Pelatihan Membuat Konten Instagram pada Karang Taruna Sedatigede - Fibriana, Adinda Herna; Rochmaniah, Ainur; Febriana, Poppy (Universitas Nusantara PGRI Kediri, 2024)
Karang Taruna Sedatigede is one of the most advanced youth organizations in Sidoarjo, judging by their programs. Karang Taruna Sedatigede uses Instagram as one of the media in promoting their activities. However, when viewed from a distance their account posts look less productive and the content is only in the form of pictures. So that it is necessary to increase the productivity of Instagram content for promotion to support the dissemination of information regarding work programs at Karang Taruna Sedatigede. From this, the community service activity